Inter‐individual variability in response to exercise intervention or usual care in hospitalized older adults. Issue 6 (13th August 2019) - Sáez de Asteasu, Mikel L.; Martínez‐Velilla, Nicolás; Zambom‐Ferraresi, Fabricio; Casas‐Herrero, Álvaro; Cadore, Eduardo L.; Ramirez‐Velez, Robinson; Izquierdo, Mikel
Abstract: Background: Exercise protocols applied during hospitalization can prevent functional and cognitive decline in older adults. The purpose of this study was to examine the individual response of acutely hospitalized patients to usual care and to physical exercise on functional capacity, muscle strength, and cognitive function and to assess the relationship with mortality at 1 year post‐discharge. Methods: In a single‐blind randomized clinical trial, 370 hospitalized patients [56.5% women; mean age (standard deviation) 87.3 (4.9) years] were allocated to an exercise intervention group (IG, n = 185) or a control group (CG, n = 185). The participants were older adults aged 75 years or older in an acute care unit in a tertiary public hospital in Navarra, Spain. The usual care group received habitual hospital care, which included physical rehabilitation when needed. The in‐hospital intervention included individualized multicomponent exercise training programme performed during 5–7 consecutive days (two sessions/day). Functional capacity was assessed with the Short Physical Performance Battery (SPPB) test and the Gait Velocity Test (GVT). Handgrip strength and cognitive function were also measured at admission and discharge. Patients in both groups were categorized as responders (Rs), non‐responders (NRs), and adverse responders (ARs) based on the individual response to each treatment during hospitalization. Results: The prevalence of Rs was higher and the prevalence of NRs and ARs was lower in the intervention group than in the control group for functional capacity (SPPB IG: Rs 85.3%, NRs 8.7%, ARs 6.0% vs. CG: Rs 37.9%, NRs 28.8%, ARs 33.3% and GVT IG: Rs 51.2%, NRs 47.3, ARs 1.6% vs. CG: Rs 18.0%, NRs 67.7%, ARs 14.3%), muscle strength (IG: Rs 62.3%, NRs 26.5%, ARs 11.3% vs. CG: Rs 20.0%, NRs 38.0%, ARs 42.0%), and cognition (IG: Rs 41.5%, NRs 57.1%, ARs 1.4% vs. CG: Rs 13.8%, NRs 76.6%, ARs 9.7%) (all P < 0.001). The ARs for the GVT in the control group and the ARs for the SPPB in the intervention group had a significantly higher rate of mortality than the NRs and Rs in the equivalent groups (0.01 and 0.03, respectively) at follow‐up. Conclusions: Older patients performing an individualized exercise intervention presented higher prevalence of Rs and a lower prevalence of NRs and ARs for functional capacity, muscle strength, and cognitive function than those who were treated with usual care during acute hospitalization. An adverse response on functional capacity in older patients to physical exercise or usual care during hospitalization was associated with mortality at 1 year post‐discharge.